Sustainability Literacy on Food Waste Education: A Preliminary Study - Rachman, Indriyani; Saldiana, Nur Kamila; Permanasari, Anna (Universitas Diponegoro, 2025)
Food waste contributes significantly to global greenhouse gas (GHG) emissions and reflects low sustainability awareness, particularly in developing countries such as Indonesia. This study aimed to assess the level of sustainability literacy, comprising knowledge, skills, and values, among vocational high school students in Bogor City within the context of food waste. Using a descriptive quantitative method with 125 respondents, data were collected through a 21-item questionnaire and were analyzed using descriptive statistics. The findings show that while students demonstrated good sustainability skills (76.95%) and values (73.63%), their sustainability knowledge was only fair (57.81%), indicating a cognitive-behavioral gap. Spearman's correlation analysis revealed no significant relationship between sustainability knowledge and skills (ρ = 0.109, p = 0.226), reinforcing the need for holistic and integrative learning interventions. These results underscore the importance of developing interactive, value-driven educational media, such as e-books, to enhance students' environmental literacy and foster sustainable behavior. This preliminary study serves as a foundation for designing contextually relevant educational strategies to support food waste reduction and sustainability education in Indonesia.